Structural transitions and magnetocaloric properties of low-cost MnNiSi-based intermetallics. (March 2023) - Eggert, B.G.F.; Belo, J.F.H.; Araújo, J.P.; Hauback, B.C.; Frommen, C.
Abstract: A series of Mn1-x Ni1-x Fe2x Si0.95 Al0.05 MM'X-type compounds (with x = 0.28, 0.3, 0.32 and 0.35) were investigated for their potential as magnetocaloric materials. Structural and magnetic properties were studied by magnetometry, microscopy and X-ray diffraction. Double substitution of Fe in Mn and Ni sites allowed to tune martensitic transition temperatures between low temperature orthorhombic and high temperature hexagonal structures from 373 K in x = 0.28–183 K in x = 0.35 during cooling. Transition temperatures occur around room temperature for x = 0.30 (300 K for cooling transformation) and 0.32 (270 for heating transformation). Isothermal entropy changes of −8, −19 and −26 J/kg.K were calculated for field changes of μ0 H = 0–2, 0–5 and 0–7 T for x = 0.30. The values are comparable to those reported for MnNi(SiAl)-based compounds with single site substitutions (Mn and Ni) by Fe. Further analyses show that high magnetic fields are necessary to induce the magnetostructural transition in all studied compounds, which can be attributed to the presence of secondary phases and/or disorder at a local level. Highlights: Novel MnNiSi intermetallics with low-cost Fe and Al substitutions are reported. Compounds feature magnetostructural transitions at room temperature. Structural, microstructural, caloric and magnetic properties are evaluated.